Dynamic Loan Loss Provisions in Uruguay : Properties, Shock Absorption Capacity and Simulations Using Alternative Formulas - Wezel, Torsten (IMF Working Papers; Working Paper ;, 2010)
This paper assesses the merits of countercyclical loan loss provisioning in Uruguay. Using a stress test methodology, it quantifies the protection against macroeconomic shocks provided by the stock of dynamic provisions accumulated since 2001 and finds that medium-sized shocks would be fully absorbed, offsetting the additional costs caused by rising specific provisions. In addition, the paper simulates the path of dynamic provisions under the formulas used in Spain, Peru and Bolivia, showing that the alternative paths diverge significantly from the actual buildup and in part better conform to the Uruguayan credit cycle.